PENGARUH ENDORSEMENT (VIA VALLEN) DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK TOLAK ANGIN CAIR DI APLIKASI MEDIA SOSIAL INSTAGRAM - Dewi Kurniawati; Ari Ahmad Sahril; Harimurti Wulandjani (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2022)
This study aims to determine whether endorsement and brand image affect consumer purchasing decisions on Instagram application. The object of this study was conducted on followers of the official account of the wind, namely @tolak_angin in the social media application Instagram with a total of 100 respondents. This data was obtained from a questionnaire and tested using the classic assumption test, multiple linear regression test, and hypothesis testing using t-test and f-test. This research also proves that partially the endorsement of consumer purchasing decisions has a strong influence. This study also states that brand image has an influence on consumer purchasing decisions. Endorsement and brand image contribute to influence consumer purchasing decisions on Reject Liquid Wind products with an adjusted R square value of 49.32%.